2017
DOI: 10.1016/j.geoderma.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Response of water extractable organic matter and its fluorescence fractions to organic farming and tree species in poplar and robinia-based alley cropping agroforestry systems

Abstract: Organic farming and agroforestry both have the potential to develop sustainable and environmental-friendly agroecosystems and to sequester more soil organic C (SOC). In a long-term field trial, we evaluated the effect of 21-year organic farming and 4-year agroforestry (Robinia and Poplar-based alley cropping system) on water extractable organic matter (WEOM). The technique combining excitation emission matrix (EEM) spectra with parallel factor analysis (PARAFAC) was used to reveal the components of WEOM. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
7
1
1
Order By: Relevance
“…2); lower than the estimated average for arable soils (i.e. 1.50-1.90) (Hassouna et al, 2012;Sun et al, 2017). Terrestrial, plant-derived material dominated DOM fluorescence (Cory and McKnight, 2005); our sampling scheme was perhaps not deep enough to catch microbial, autochthonous signatures of DOM occurring in subsoil layers (Hassouna et al, 2012).…”
Section: Tablementioning
confidence: 74%
“…2); lower than the estimated average for arable soils (i.e. 1.50-1.90) (Hassouna et al, 2012;Sun et al, 2017). Terrestrial, plant-derived material dominated DOM fluorescence (Cory and McKnight, 2005); our sampling scheme was perhaps not deep enough to catch microbial, autochthonous signatures of DOM occurring in subsoil layers (Hassouna et al, 2012).…”
Section: Tablementioning
confidence: 74%
“…A high BIX (>1) is attributed to a predominantly autochthonous origin of WEOM and to the presence of OM freshly released into water, whereas a low BIX indicates lower autochthonous WEOM production. In addition, decomposition of the autoch- [31] and in organic farming and agroforestry soils (around 0.76) [18]. This observation suggested that the WEOM pool in these soil samples were contributed mainly from decomposed plant residues and little WEOM was derived from the fresh active crop root and indigenous microbial exudates.…”
Section: Fluorescence Parametersmentioning
confidence: 97%
“…The lower PLF values suggested the interference of PLF on HIX was minimal. BIX is referred as an indicator of the presence of autochthonous biological activity [23] [34], BIX has also been called a "freshness indicator" [18]. A high BIX (>1) is attributed to a predominantly autochthonous origin of WEOM and to the presence of OM freshly released into water, whereas a low BIX indicates lower autochthonous WEOM production.…”
Section: Fluorescence Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinia menunjukkan efek positif pada kandungan carbon dalam tanah dan nitrogen total dibanding poplar, dan memiliki efek lebih kuat pada komponen kandungan bahan organik, walaupun tidak berbeda antara dua jenis pohon. Dari sini diketahui pula, penyebaran bakteri organik dan mikroorganisme bermanfaat bagi pengembangan sistem pertanian dan penyerapan karbon tanah (Sun et al, 2017). Neupane and Thapa (2001) Tanaman hedgerow yang digunakanGliricidia sepium, Paspalum conjugatum, dan Penisetum purpureum.…”
Section: Daur Ulang Hara Dan Kemampuan Tanah Menyimpan Airunclassified